2019
DOI: 10.19139/soic.v7i1.512
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Factor Analysis for Software Development Projects in Mexico

Abstract: Time and risk management have always been major concerns in a continously growing number of processes and methodologies used to develop all kinds of useful products and services. Software like any other industry not only needs the most appropriate development methodology but also an efficient project management strategy that is capable of estimating and managing development times and any potential risks as best as possible in order to deliver high quality software products and services on time. Hence, the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In these regressions the variance inflation factor values were lower than 5 and the tolerance indexes were neither close to 0 nor above 1, which ruled out any concerns about multicollinearity. 102 To test whether the relationship between specific independent variables and compliance intentions were contingent on social group, we added interactions between these variables and the social group in an OLS regression that included the entire sample.…”
Section: Methodsmentioning
confidence: 99%
“…In these regressions the variance inflation factor values were lower than 5 and the tolerance indexes were neither close to 0 nor above 1, which ruled out any concerns about multicollinearity. 102 To test whether the relationship between specific independent variables and compliance intentions were contingent on social group, we added interactions between these variables and the social group in an OLS regression that included the entire sample.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the existing literature indicated that the BA2 (lack of economic maturity) is a barrier in the execution of the RE process [53]. Khan et al [4] indicated that most of the vendor firms face budget problems, and they do not consider the RE process as an important activity in software development.…”
Section: Literature Review (Rq 1)mentioning
confidence: 99%
“…Most of the existing literature indicated that the BA2 (lack of economic maturity) is a barrier in the execution of the RE process [53]. Khan et al.…”
Section: Findings Of the Studymentioning
confidence: 99%